A systematic review of predictors and moderators of improvement in cognitive-behavioral therapy for panic disorder and agoraphobia. (December 2015) - Porter, Eliora; Chambless, Dianne L.
Abstract: Background: Despite the considerable efficacy of cognitive-behavioral therapy (CBT) for panic disorder (PD) and agoraphobia, a substantial minority of patients fail to improve for reasons that are poorly understood. Objective: The aim of this study was to identify consistent predictors and moderators of improvement in CBT for PD and agoraphobia. Data sources: A systematic review and meta-analysis of articles was conducted using PsycInfo and PubMed. Search terms included panic, agoraphobi *, cognitive behavio *, CBT, cognitive therapy, behavio * therapy, CT, BT, exposure, and cognitive restructuring . Study selection : Studies were limited to those employing semi-structured diagnostic interviews and examining change on panic- or agoraphobia-specific measures. Data extraction: The first author extracted data on study characteristics, prediction analyses, effect sizes, and indicators of study quality. Interrater reliability was confirmed. Synthesis: 52 papers met inclusion criteria. Agoraphobic avoidance was the most consistent predictor of decreased improvement, followed by low expectancy for change, high levels of functional impairment, and Cluster C personality pathology. Other variables were consistently unrelated to improvement in CBT, understudied, or inconsistently related to improvement. Limitations: Many studies were underpowered and failed to report effect sizes. Tests of moderation were rare. Conclusions: Apart from agoraphobic avoidance, few variables consistently predict improvement in CBT for PD and/or agoraphobia across studies. Highlights: Agoraphobic avoidance predicted less improvement from pre- to post-treatment. Functional impairment and low expectancy for change predicted less improvement. Comorbid depression and medication use consistently did not predict improvement. Few studies examined moderators of improvement in CBT vs. other treatments.